Biomechanical and Clinical Validation of a Modulus-Graded Ti-Nb-Sn Femoral Stem for Suppressing Stress Shielding in Total Hip Arthroplasty - Yu Mori; Hidetatsu Tanaka; Hiroaki Kurishima; Ryuichi Kanabuchi; Naoko Mori; Keisuke Sasagawa; Toshimi Aizawa (Applied Sciences)
Stress shielding remains a major concern in cementless total hip arthroplasty (THA) due to the stiffness mismatch between femoral stems and surrounding bone. This study investigated the biomechanical and clinical performance of a novel Ti-33.6Nb-4Sn (Ti-Nb-Sn) alloy stem with a graded Young’s modulus achieved through localized heat treatment. A finite element model (FEM) of the Ti-Nb-Sn stem, incorporating experimentally validated Young’s modulus gradients, was constructed and implanted into a patient-specific femoral model. Stress distribution and micromotion were assessed under physiological loading conditions. Clinical validation was performed by evaluating radiographic outcomes at 1 and 3 years postoperatively in 40 patients who underwent THA using the Ti-Nb-Sn stem. FEM analysis showed low micromotion at the proximal press-fit region (4.89 μm rotational and 11.74 μm longitudinal), well below the threshold for osseointegration and loosening. Stress distribution was concentrated in the proximal region, effectively reducing stress shielding distally. Clinical results demonstrated minimal stress shielding, with no cases exceeding Grade 3 according to Engh’s classification. The Ti-Nb-Sn stem with a gradient Young’s modulus provided biomechanical behavior closely resembling in vivo conditions and showed promising clinical results in minimizing stress shielding. These findings support the clinical potential of modulus-graded Ti-Nb-Sn stems for improving implant stability in THA.